Penambahan ekstrak kunyit (Curcuma domestica Val) cair terhadap karakteristik organoleptik dan kandungan antioksidan krispi bayam (crispy spinach) - Hari Hariadi; Asysyifa Riana; Tisya Aisyah Chaerunnisa; Suseno Amien; Yusep Ikrawan; Triana Ulfah; Judiono Judiono; Cahya Edi Wahyu Anggara; Ilman Wibawa; Widiawati Widiawati; Duhita Diantiparamudita Utama (University of Insan Cendekia Mandiri, 2023)
The human immune system can protect the body from bacteria, viruses, and parasites that cause disease. The immune system becomes more active when enough amounts of macro and micro nutrients are consumed. Antioxidants can also guard against the attack of free radicals and radical chemicals found in the body, limiting the damage caused by the oxidation process. One of them is using turmeric and spinach extract as a supplement. Turmeric extract can be used in the production of crispy spinach cookies. The research was purposed to find out the effect of turmeric extract addition on organoleptic characteristics and antioxidant content crispy spinach. This research used a Experimental research design (Pre-Experimental Design) with three treatments consisting of the addition of 50 ml, 60 ml, and 70 ml of turmeric extract. All three formulations were conducted hedonic tests for know the best formulation, followed by antioxidant content (DPPH method), carbohydrate content (method by different), protein content (Kjedahl), and fat content (Soxhlet). Furthermore, economic analysis and product ranking are carried out. Formulation 3 was chosen because of the highest nutritional content. Keywords: crispy spinach, immunity, turmeric extract